Palmyra Wanderley e a educação da mulher no cenário Norte-rio-grandense (1914 -1920) - Carvalho, Isabel Cristine Machado de (2005)
The present work has the intention to analyze the contribution of the writer and journalist Palmyra Guimarães Wanderley to the education, throughout her writings in the period between 1914 to 1920. I search through her journalist writings produced in the feminine magazine Via Láctea (1914-1915) her idealization, and as in the newspaper A República e Diário de Natal, in the decade of 1920 establishing relationships with education, mostly because of her production in the pages of the paper articles regarding feminine education and women condition. At the same time I sketch the biographic profile of Palmyra Wanderley relating her to the historical moment that she lived. To achieve the proposed goals I begin with a documental research within the available archives and use other sources like pictures and interviews with her relatives. The results of the research show that the worry of Palmira Wanderley with the education in our state, goes beyond her published writings in magazines and newspapers. She has been ahead of Escola de Comércio Feminino and Aliança Feminina, she has also done a conference in the House of the Young Single Ladies' Protection (Casa de Proteção às Moças Solteiras), institution of the Aliança s responsibility that offered shelter, food, formal and religious education to the workers of the Fabric Factory of Natal (Fábrica Tecidos de Natal). Her involvement evidences her contribution to the historiography of the education in Rio Grande do Norte, specially the history of women education ensuring her presence in the day by day history